2021
DOI: 10.1016/j.cjco.2020.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Immunosuppression on Left Ventricular Recovery and Mortality in Fulminant Viral Myocarditis: A Case Series and Review of Literature

Abstract: Background Fulminant viral myocarditis (FVM) is a rare cause of cardiogenic shock associated with high morbidity and mortality rates. An inappropriately activated immune system results in severe myocardial inflammation. Acute immunosuppressive therapy for FVM therefore gained in popularity and was described in numerous retrospective studies. Methods We conducted an extensive review of the literature and compared it with our single-centre retrospective review of all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The rationale for the MYTHS trial is based on clinical practice. Indeed, several case series and case reports support the effectiveness of high dosage corticosteroids ( 48 50 ).…”
Section: Lymphocytic Myocarditismentioning
confidence: 99%
“…The rationale for the MYTHS trial is based on clinical practice. Indeed, several case series and case reports support the effectiveness of high dosage corticosteroids ( 48 50 ).…”
Section: Lymphocytic Myocarditismentioning
confidence: 99%
“…The gold standard for diagnosis is via histopathological sampling with endomyocardial biopsy, however, this is not always feasible or practical. A probable diagnosis can be achieved in the appropriate clinical context with elevated cardiac enzymes as well as functional and structural abnormalities on cardiac echocardiogram and MRI [1] .…”
Section: Discussionmentioning
confidence: 99%
“…The strongest evidence for immunosuppressive therapy occurs in cardiac sarcoidosis, giant-cell myocarditis, and autoimmune rheumatic disease ( 22 24 ). However, recent studies in adults and pediatrics reported that immunosuppressive therapy with IVIG and/or high dose methylprednisolone was associated with rapid LVEF recovery, short duration of ECMO support, and low mortality rate in fulminant myocarditis ( 25 , 26 ). Nevertheless, further well-designed studies are required to investigate this issue in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%